The Future of News: Building and Using Information Services in Connection with Newspapers - Önal, H. İnci (Information World, 2007)
The purpose of the present research is to specify the current stand and future of information services in providing news. Libraries and archives that collect newspapers, and supply services to let the readers to have quick and easy access to their contents, increase their activities and in conjunction to this, their experience. As an initial step of the present research, by methods of interviewing and administering questionnaires, Ankara branch office responsible of six nationwide distributed daily newspapers were investigated. Data were compiled about the present situation, provided services, problems to be confronted, and work plans. According to the evaluations, it seems that the developments in information technologies would also impose important tasks to libraries in case of disseminating newspaper information.
Keywords: News; Information management; Newspapers; Journalism